2016
DOI: 10.1371/journal.pntd.0005032
|View full text |Cite
|
Sign up to set email alerts
|

The Sero-epidemiology of Coxiella burnetii in Humans and Cattle, Western Kenya: Evidence from a Cross-Sectional Study

Abstract: Evidence suggests that the intracellular bacterial pathogen Coxiella burnetii (which causes Q fever) is widespread, with a near global distribution. While there has been increasing attention to Q fever epidemiology in high-income settings, a recent systematic review highlighted significant gaps in our understanding of the prevalence, spatial distribution and risk factors for Q fever infection across Africa. This research aimed to provide a One Health assessment of Q fever epidemiology in parts of Western and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 45 publications
8
77
3
Order By: Relevance
“…For example, in West Africa looking at Fulani cattle herds (Adesiyun, Jagun, Kwaga, & Tekdek, ; Adesiyun, Jagun, & Tekdek, ), in the Adamawa region of Cameroon (Scolamacchia et al, ), in southeastern Ethiopia (Gumi et al, ), and in the Central African Republic (Nakouné et al, ) reported 32%–55%, 31%, 32% and 14% C. burnetii seroprevalence values, respectively. Within Kenya, two studies of cattle reported C. burnetii seroprevalence values of 28% and 11% (Knobel et al, ; Wardrop et al, ), but both of these studies were done in western Kenya in an area ecologically and economically very different from Laikipia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in West Africa looking at Fulani cattle herds (Adesiyun, Jagun, Kwaga, & Tekdek, ; Adesiyun, Jagun, & Tekdek, ), in the Adamawa region of Cameroon (Scolamacchia et al, ), in southeastern Ethiopia (Gumi et al, ), and in the Central African Republic (Nakouné et al, ) reported 32%–55%, 31%, 32% and 14% C. burnetii seroprevalence values, respectively. Within Kenya, two studies of cattle reported C. burnetii seroprevalence values of 28% and 11% (Knobel et al, ; Wardrop et al, ), but both of these studies were done in western Kenya in an area ecologically and economically very different from Laikipia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cattle have found that proximity to water is a risk for C. burnetii infection and that seroprevalence in cattle correlates with precipitation levels (Czaplicki et al, ); (Ellen et al, ; Wardrop et al, ). West African sites reported higher antibody seroprevalence values than drier Sahelian regions (Adesiyun et al, ; Schelling et al, ), while wetter western Kenyan sites reported higher antibody seroprevalence values than Laikipia (Knobel et al, ; Wardrop et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Laikipia County showed a distinct seroprevalence gradient, with seroprevalence ranging from 0% to 4% in cattle, 13% to 20% in sheep, 31% to 40% in goats and 5% to 46% in camels (DePuy et al., ). A recent linked human–cattle population survey in western Kenya detected prevalence of 2.5% in humans and 10.5% in cattle (Wardrop et al., ).…”
Section: Introductionmentioning
confidence: 99%